ANALISIS KRIMINOLOGI TERHADAP PERILAKU GENG MOTOR SEBAGAI BENTUK KENAKALAN REMAJA DI KOTA PALU - Jufri, Muhammad (Katalogis, 2015)
This study aims to determine the factors that cause the motorcycle gang to commit crimes in the city of Palu and effort penanggunalangannya and motorcycle gang behavior as a form of delinquency of criminological perspective. This research was conducted in the city of Palu with empirical legal research methods. Data collection through field study is to conduct interviews and circulate koesiner. Data analysis technique used qualitative analysis. The results showed that the factors causing the motorcycle gang to commit crimes in the city of Palu due to the low level of education, as well as the age of the perpetrators are still juvenile, social environment adolescents unfavorable conditions less harmonious family and the lack of supervision from parents, in addition to the influence of mass media which is often menanyangkan violence. Efforts to control the crimes committed by motorcycle gangs carried out with effort pre-emptive such as the planting of values ​​and norms that both the adolescents, establishing a harmonious relationship between the fellow members of your family and choose the social environment is good, preventive measures such as the activation of positive activities for young people, raid and counseling to schools and efforts of repressive sanctions and the provision of guidance. While the behavior of a motorcycle gang in the city of Palu as a form of delinquency among others to disturb public order, action mugging and persecution.